Surface and depth : dialectics of criticism and culture - Shusterman, Richard (Cornell University Press, 2002)
A paradox of surface and depth pervades the field of aesthetics. How can art's surface meanings and qualities be properly appreciated without understanding the cultural context that shapes their creation and perception? But exploring such underlying cultural conditions challenges the perception of thosequalities and meanings of aesthetic surface that constitute the captivating power of art. If aesthetics deals with both surface and depth, impassioned immediacy yet also critical distance of judgment, how can this doubleness be held together in one philosophical vision?In his new book, Richard Shusterman explores the dialectics of surface and depth by examining key issues in the philosophy of art and culture-from the logic of interpretation and evaluation to the roots of taste and convention, from the meanings of aesthetic purity and immediacy to the role of nature, theory, and history in our experience and understanding of art. In treating these topics, Shusterman combines the methods of analytic philosophy, critical theory, and poststructualism to arrive at new positions, displaying the philosophical versatility, originality of vision, and graceful, accessible writing that have become his trademark. Surface and Depth is crowned by a new definition of art as dramatization.